GE_GERICHTE P/3709/2013 vom 1. Februar 2016 - GE Cour de justice (2016)
IN DUBIO PRO DURIORE ; LEX MITIOR ; PORNOGRAPHIE ; PORNOGRAPHIE DURE ; ON-LINE ; SITE INTERNET ; INTERNET ; TÉLÉCHARGEMENT ; INFORMATIQUE | CP.2; CP.197; CP.197.5; aCP.197.3; aCP.197.3bis